Information aggregation through stock prices and the cost of capital - Olga Gorelkina; Wolfgang Kuhle (Max Planck Institute for Research on Collective Goods, 2013)
This paper studies a firms optimal capital structure in an environment, where the firms stock price serves as a public signal for its credit worthiness. In equilibrium, equity investors choose how much information to acquire privately, which induces a positive relation between the amount of equity issued and the stock price signals precision. Thus, through its capital structure, the firm can internalize the informational externality that stock prices exert on bond yields. Firms with a strong fundamental therefore issue more equity and less debt than they would if the informational spill-over did not exist.
Keywords: G32; D83; C73; G10; 330; information aggregation; capital structure; sequential markets; market depth